Background reconstruction: approaches to the first women of santafesino social work (Papeles, 2025)
The histories of professions require exhaustive work that allows us to understand the multiple facets that traverse them. Specifically in Social Work and professions practiced predominantly by women, the issue of gender is inherent to the analysis, given that these professions are not neutral. From situated readings and analyses, it is possible to understand and value the trajectories and contributions of social work actors; and—fundamentally—to conduct interpretations of the professionalization process in general, recovering part of the local history of social service.This article arises from the thesis project entitled "Pioneers of Social Work in Santa Fe: Ángela Teresa Vigetti, her trajectories and contributions to the professionalization process," whose general objective is to analyze the trajectory and contributions of this protagonist from the early professional era of social work in Santa Fe, during the period 1943–1971. To this end, this paper contextualizes the research issue by reconstructing the problem and retrieving background information, which allows for contributions, dialogue, and finding gaps from which to pose new questions.